A descriptive-contrastive analysis of Ilongo Hiligaynon and English personal pronouns - Gobuyan, Erlinda A. 1936- (s.n.], 1966)
This study identified the basic differences in the features of the personal pronouns of Ilongo Hiligaynon and English. It was assumed that the difference in whatever feature in the languages being compared will ultimately become teaching problems for native speakers learning the second language.